(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
In this paper, the authors explore the impact of the business environment on the microeconomic competitiveness of companies in the dairy industry sector in Bosnia and Herzegovina. The business environment in which these enterprises operate may be a motivating force or, on the other hand, a limiting factor of their progress. The study examines the variables of the business environment and the variables of the microeconomic competitiveness and their interconnection. The results of the empirical research confirm the earlier findings and results of similar research on the unfavorable business environment in Bosnia and Herzegovina. Complete statistical data processing was done on a sample of 26 enterprises (84% of the total population) operating in that sector, by the method of correlation analysis and multiple linear regression. In that sense, the influence of movement, tax rate, the number of procedures for the establishment of the company, the time of export, the time of import, and the number of procedures for obtaining building permits were examined as indicators of an independent variable, on the movement of microeconomic competitiveness as a dependent variable by means of the multiple regression analysis. For this purpose, one central and three working hypotheses, as well as 3 linear regression models, are set up, which will help in deciding or rejecting the set hypotheses.